(untitled) (Analele Universității din București. Științe Politice, 2025)
This paper explores the Dutch seduction community in an effort to understand how its members’ inter-subjective frameworks relate to wider issue of sexual violence. Part of the men’s rights movement, the seduction community is a transnational, self-help community aiming at empowering men who are “deficient” at social skills and particularly at successfully “picking up” women. The embodiment of masculinity is central to this rule-based, essentialist framing of sexuality and attraction in which men aim at instrumentally influencing sexual interactions in a quest to regain control and felt lost power over intimate relations. Sexual success becomes a token of manhood that not only helps “socially awkward heterosexual men” climb up the social ladder of masculinities but also one that promises soothing of anxieties and mastering of emotions. Based on twelve qualitative interviews of the Dutch seduction community’s members, this paper examines how its members frame their involvement with pickup in light of the anti-sexual harassment activism represented by MeToo. The paper argues that the community resorts to an intertwining of two complementary discursive frameworks: hegemonic masculinity versus victim power, emphasizing what scholars have called hybrid masculinity.